2017
DOI: 10.1364/boe.8.002324
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescein as a topical fluorescent contrast agent for quantitative microendoscopic inspection of colorectal epithelium

Abstract: Abstract:Fiber bundle microendoscopic imaging of colorectal tissue has shown promising results, for both qualitative and quantitative analysis. A quantitative image quality control and image feature extraction algorithm was previously designed for quantitative image feature analysis of proflavine-stained ex vivo colorectal tissue. We investigated fluorescein as an alternative topical stain. Images of ex vivo porcine, caprine, and human colorectal tissue were used to compare microendoscopic images of tissue top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…MB was used for the first time by Ehrlich, in 1886, to stain the nervous tissue by injecting it intravenously into a living animal [11]. As a non-toxic biological stain, with an affinity for mucosal tissue [9], nowadays, MB is used for nervous tissue and endocrine gland identification during surgery [19]. Meanwhile, PRO is used to highlight the cell nuclei and enable direct visualization of cellular morphology without removing the tissue, on behalf of its property as a topical contrast agent [36].…”
Section: Preoperative and Intraoperative Use In Cardiac Surgerymentioning
confidence: 99%
See 4 more Smart Citations
“…MB was used for the first time by Ehrlich, in 1886, to stain the nervous tissue by injecting it intravenously into a living animal [11]. As a non-toxic biological stain, with an affinity for mucosal tissue [9], nowadays, MB is used for nervous tissue and endocrine gland identification during surgery [19]. Meanwhile, PRO is used to highlight the cell nuclei and enable direct visualization of cellular morphology without removing the tissue, on behalf of its property as a topical contrast agent [36].…”
Section: Preoperative and Intraoperative Use In Cardiac Surgerymentioning
confidence: 99%
“…Different authors reported the use of both dyes for diagnostic procedures including: in vivo confocal laser endomicroscopy [37,38], in vivo microscopy to identify Barrett's esophagus [39], pathological changes in oral mucosa [40], colon [9], stomach [41], duodenum, upper gastrointestinal tract [41] and central airway, cervical tissue [35,42], cervix [35], sarcoma [43], urinary fistula [44], sentinel node (SN)'s, head and neck cancers [45], breast cancer [17], and gastrointestinal and thyroid surgery [10]. Apart from MB and PRO's ability to stain nuclei, the latter also stains non-specifically the membranes of adipocyte cells, making it possible to identify adipocytes without using a contrast agent [43].…”
Section: Preoperative and Intraoperative Use In Cardiac Surgerymentioning
confidence: 99%
See 3 more Smart Citations